EKSPERIMEN KINETIKA ENZIM MENGGUNAKAN MODEL INKUIRI TERBIMBING UNTUK MENINGKATKAN KETRAMPILAN BERPIKIR KREATIF MAHASISWA - Nadia Amida; F.M. Titin Supriyanti; Liliasari Liliasari (University of Bengkulu, 2018)
[EXPERIMENT OF ENZYME KINETICS USING GUIDED INQUIRY MODEL FOR ENHANCING CREATIVE THINGKING SKILLS] Purpose of this study was enhancing creative thinking skills of students using guided inquiry model through experiments of enzyme kinetics based on local materials. Method of this research was quasi-experimental methods, with pretest-posttest nonequivalent control group design. Subjects of this study were chemistry students enrolled in biochemistry lab course, consisted of 18 students in the experimental class and 19 students in control class. Instrument in this study were essay test that involves 3 indikators of creative thinking skills (i.e. fluency, flexibility, and elaboration) and also student worksheets. The results showed that the experiments of kinetics enzyme using guided inquiry model have been enhance creative thinking skills in medium category with a value of N-gain average of 0.66. Two indikators classified in the high category are fluency and elaborationwith the value of N-gain 0,71. Meanwhile, indikator of flexibility in the medium category with a value of N-gain 0,56.